1997
DOI: 10.1210/en.138.4.1736
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Participates in the Remodeling of the Endocrine Pancreas in the Neonatal Rat

Abstract: In rodents, shortly after birth a lack of increase in pancreatic weight and in islet mass have been reported during a time of overall body weight increase. To understand this regulation of the neonatal growth of the beta cell mass, we studied Sprague Dawley rats at 2, 9, 13, 17, 20, 24, and 31 days of age for beta cell replication, beta cell mass, and cell size and for the presence of cell apoptosis. beta cell mass was stable from 2-20 days (range: 0.91 +/- 0.2 to 1.33 +/- 0.23 mg) and increased thereafter. be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
247
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(279 citation statements)
references
References 0 publications
26
247
6
Order By: Relevance
“…GLP-1R activation has been demonstrated both in human islets in vitro and in rodent models in vivo to reduce β cell apoptosis. The rate of β cell apoptosis is very low (Scaglia et al, 1997) and therefore models of injury to the endocrine pancreas have to be used to measure potential protective effects of GLP-1R agonists against the demise of the β cell. The first published model was the inbred Zucker diabetic fatty rat (ZDF/GmiTM-fa/fa, previously described in section 6.1) to which GLP-1 was infused over 2 days (Farilla et al, 2002).…”
Section: β Cell Toxicity and Death: Protective Effects Of Glp-1r Agonmentioning
confidence: 99%
“…GLP-1R activation has been demonstrated both in human islets in vitro and in rodent models in vivo to reduce β cell apoptosis. The rate of β cell apoptosis is very low (Scaglia et al, 1997) and therefore models of injury to the endocrine pancreas have to be used to measure potential protective effects of GLP-1R agonists against the demise of the β cell. The first published model was the inbred Zucker diabetic fatty rat (ZDF/GmiTM-fa/fa, previously described in section 6.1) to which GLP-1 was infused over 2 days (Farilla et al, 2002).…”
Section: β Cell Toxicity and Death: Protective Effects Of Glp-1r Agonmentioning
confidence: 99%
“…In rodents, the endocrine cell population undergoes a dramatic expansion beginning at embryonic day 14.5 followed by remodelling, during which there is regulated alteration in apoptosis and neogenesis and a progressive decrease in beta cell replication [16].…”
Section: Prenatal and Neonatal Periodmentioning
confidence: 99%
“…It has been demonstrated in the low protein model that islet vascularisation was dramatically reduced in neonates of low protein dams (37) as was the number and volume density Page 11 of 21 A c c e p t e d M a n u s c r i p t 11 (38). Shortly after birth a wave of apoptosis and remodelling of the beta cells occurs (67,68). It has now been shown that new beta cells arise from the proliferation of existing beta cells (69) as well as differentiating acinar cells (70).…”
Section: The Role Of the Pancreatic Beta Cell In Glucose/insulin Metamentioning
confidence: 99%